Activation of HLS1 by Mechanical Stress via Ethylene-Stabilized EIN3 Is Crucial for Seedling Soil Emergence - Shen, Xing; Li, Yanli; Pan, Ying; Zhong, Shangwei (Frontiers in Plant Science, 2016)
The seeds of terrestrial flowering plants often start their life cycle in subterranean darkness. To protect the fragile apical meristematic tissues and cotyledons from mechanical injuries during soil penetration, dicotyledonous seedlings form an elegant apical hook at the top of the hypocotyl. The apical hook has been considered as an adaption structure to the subterranean environment. However, the role of the apical hook in seedling emergence and the molecular mechanism of apical hook formation under real-life conditions remain highly speculative. Here, we find that HOOKLESS 1 (HLS1), a critical gene in apical hook formation in Arabidopsis thaliana, is required for seedling emergence from the soil. When grown under soil, hls1 mutant exhibits severe emergence defects. By contrast, HLS1 overexpression in the hls1 background fully restores emergence defects and displays better emergence capacity than that of WT. Our results indicate that HLS1 transcription is stimulated in response to the mechanical stress of soil cover, which is dependent on the function of the transcription factors ETHYLENE INSENTIVE 3 (EIN3) and EIN3-LIKE 1 (EIL1). Soil-conferred mechanical stress activates the ethylene signaling pathway to stabilize EIN3 by repressing the activity of the F-box proteins EBF1 and EBF2. These combined results reveal a signaling pathway in which plant seedlings transduce the mechanical pressure of soil covering to regulate apical hook formation accordingly for emerging from the soil.